PENDIDIKAN KARAKTER SISWA SEKOLAH DASAR MELALUI PEMBELAJARAN SENI BUDAYA - Hartini Hartini; Dewi Tryanasari; Endang Sri Maruti (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2015)
The character is a distinctive personality of each individual to live and work, both in the scope of the family, community, nation and state. Arts and culture in elementary school in 2004 as a core curriculum capacity building in the field of aesthetics has a potential role to support and realize the whole Indonesian human character. This study describes the implementation and building constraints positive character of students in arts and culture in SDN Jogodayuh 1, District Geger, Madison County. This study used a qualitative research design with a phenomenological approach. Triangulation of data is done by using triangulation and triangulation methods. The results of this study indicate that many of the benefits obtained by the students in the study of art and culture in primary schools include: (1) deepen wonderfully flavors, (2) knowledge of the objective and subjective elements, (3) strengthen the love for the arts and culture, (4) foster subtlety of flavor, (5) deepen the culture, (6) assess the work of art, (7) awareness on the negative effects, (8) to strengthen public confidence, (9) discipline, and (10) provide extensive insight and provision for spiritual and psychological life.